Factors Affecting the Financial Performance in the Banking Sector Listed on the Indonesia Stock Exchange - Dhea Fransisca; Sri Wahyuni; Eko Hariyanto; Ani Kusbandiyah (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to examine the effect of Third Party Funds, Operating Expenses Operating Income, Capital Adequacy Ratio, Loan to Deposit Ratio and Firm Size on Financial Performance in the Banking Sector Listed on the Indonesia Stock Exchange. The analytical method used is multiple linear regression. The population of this study are Commercial Banks listed on the Indonesia Stock Exchange in 2019-2021. The data used in this study is secondary data with the selection of samples using purposive sampling method. The results of the study state that the variables of Third Party Funds, Operating Expenses on Operating Income and Firm Size have no effect on Return on assets. The Capital Adequacy Ratio variable has no significant effect while the Loan to Deposit Ratio has a significant positive effect on return on assets.